2010
DOI: 10.2174/1874920801003010001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transformational Leadership on Student Educational Satisfaction and Student Stress~!2009-09-08~!2010-01-01~!2010-03-02~!

Abstract: This paper examines the effects of transformational leadership (TL) on student educational satisfaction (SES) and student stress (SS). Asian students enrolled in business management program at colleges and universities in British Columbia, Canada were surveyed to find out their perceptions as to whether TL used by faculty members improves SES and reduces SS. Results suggest that SES is positively related to the improvement in the level of perceived TL used by instructors/professors. The empirical findings of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…This study briefly explores the evolution of leadership theory, leadership during crisis, in general, and leadership during COVID-19 from a psychological perspective. Gill et al (2010) investigates the impact of transformational leadership (TL) on student educational satisfaction (SES) and student stress (SS) among Asian students pursuing business management programs in colleges and universities in British Columbia, Canada. The results demonstrate that an increase in perceived TL used by instructors/professors correlates positively with improved SES and reduced SS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study briefly explores the evolution of leadership theory, leadership during crisis, in general, and leadership during COVID-19 from a psychological perspective. Gill et al (2010) investigates the impact of transformational leadership (TL) on student educational satisfaction (SES) and student stress (SS) among Asian students pursuing business management programs in colleges and universities in British Columbia, Canada. The results demonstrate that an increase in perceived TL used by instructors/professors correlates positively with improved SES and reduced SS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In educational context, lecturers act as leaders, while students become the followers. Transformational leadership, if applied by instructors or lecturers, is expected to guarantee the success of study programs, faculties, and universities because it can increase student satisfaction in educational process [22]. It was explained that the concepts and definitions of transformational leadership are related to "leadership and performance above expectations".…”
Section: Transformational Leadership Objective Commitment Learning Mo...mentioning
confidence: 99%
“…Pounder (2008) students and discovered that increase in ratings of teachers' transformational leadership was associated with an increase in student ratings of their willingness to put in extra efforts and their satisfaction with the teachers. Gill et al, (2010) suggested that transformational leadership enhances students' educational satisfaction. Thus, in higher education, this style of leadership may improve the teaching-learning process, as well as students' satisfaction.…”
Section: Transformational Leadershipmentioning
confidence: 99%